Contraception for women with epilepsy: counseling, choices, and concerns - Reimers A (Dove Medical Press, 2016)
Arne Reimers1,2 1Department of Clinical Pharmacology, St Olavs University Hospital, 2Department of Laboratory Medicine, Children’s and Women’s Health, Faculty of Medicine, Norwegian University of Science and Technology (NTNU), Trondheim, Norway Abstract: Approximately 50% of all pregnancies in women with epilepsy (WWE) occur unplanned. This is worrying, given the increased occurrence of obstetrical complications in WWE, including the risk of seizures and their possible consequences for both the mother and the unborn child. Hormonal contraception is usually regarded as highly effective, but it is subject to numerous bidirectional drug interactions with several antiepileptic drugs. These interactions may lead to loss of seizure control or contraceptive failure. Further concerns are loss of bone mineral density and increased seizure activity due to hormonal effects. Many physicians lack sufficient knowledge regarding these issues, and most WWE have never received adequate counseling. Moreover, several studies show that a large proportion of WWE do not take their medicines regularly. This article reviews all of these issues and offers practical recommendations for the management of contraception in WWE. Keywords: ethinyl estradiol, progestins, epilepsy, antiepileptic drugs, interactions, pregnancy, seizure aggravation, bone mineral density